Development of cell culture from liver and kidney of Indian major carp, Labeo rohita (Hamilton) - Lakra, W S; Behera, M R; Sivakumar, N; Goswami, M; Bhonde, R R (Indian Journal of Fisheries, 2011)
The present study was undertaken to assess the potential of six tissues ofLabeo rohita viz. kidney, liver, heart, gill, caudal fin and swim bladder forattachment, cell outgrowth and proliferation by explant culture andtrypusinization methods. Cell outgrowth was obtained from liver explants ofL. rohita (2 months old) on ninth day. Cells radiated from liver explants grewand gave rise to colonies of individual cells. The disaggregated cells preparedby trypsinization of kidney tissue reached confluent stage nine days afterseeding. The optimum incubation temperature for the liver and kidney cellswas found to be 26-28ÂºC. Among the various media [Leibovitz-15 (L-15), M-199 and EMEM] tested, L-15 was found to be most suitable for the attachmentand cell proliferation. The media were supplemented with 15 % foetal bovineserum, 10 % fish muscle extract (FME) and 1 % fish (L. rohita) serum. DifferentpH of the growth media ranging from 7.2 to 7.8 was employed to determineoptimum values. It was found that pH 7.4 proved to be the best for growth ofcells.